1981
DOI: 10.1346/ccmn.1981.0290305
|View full text |Cite
|
Sign up to set email alerts
|

Boron Adsorption by Clay Minerals Using a Phenomenological Equation

Abstract: Abstract--Boron adsorption by Ca forms of montmorillonite, illite, and kaolinite was determined as a function ofpH and boron concentration in solution. Data from batch experiments were compared with results computed for each clay according to fitted adsorption coefficients (maximum boron adsorption and affinity constants related to the binding energy). The agreement between calculated values and experimental results indicates that a phenomenological equation can be used to predict boron adsorption on clays as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
1
4

Year Published

1982
1982
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(68 citation statements)
references
References 19 publications
5
58
1
4
Order By: Relevance
“…It should be noted that, unlike Sr 2+ , B behaves in a more conservative way and can hardly precipitate from the solution (Grew and Anovitz, 1996;Walker, 1975). Even admitting the presence of adsorption processes such as those detected in marine environments by Couch (1971), B would have been incorporated in clays' tetrahedral sheet structures at a very low rates (Keren and Mezuman, 1981) and it cannot be re-dissolved at the Ca' Lita site temperatures. Therefore, B tot contents linked to the deep water inflows could even be larger than those measured.…”
Section: Origin Of Groundwater and Deep Water Inflowmentioning
confidence: 99%
“…It should be noted that, unlike Sr 2+ , B behaves in a more conservative way and can hardly precipitate from the solution (Grew and Anovitz, 1996;Walker, 1975). Even admitting the presence of adsorption processes such as those detected in marine environments by Couch (1971), B would have been incorporated in clays' tetrahedral sheet structures at a very low rates (Keren and Mezuman, 1981) and it cannot be re-dissolved at the Ca' Lita site temperatures. Therefore, B tot contents linked to the deep water inflows could even be larger than those measured.…”
Section: Origin Of Groundwater and Deep Water Inflowmentioning
confidence: 99%
“…Although adsorption of B has been studied in numerous researches using empirical equations (Keren and Mezuman 1981;Elrashidi and O'Connor 1982;Goldberg and Forster 1991;Majidi et al 2010), B surface complexation modeling of soil constituent assemblages has less been investigated (Goldberg 1999;Goldberg et al 1993Goldberg et al , 2000Goldberg et al , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of boron between the solid and liquid phase of soil is particularly important in view of the relatively small range between levels causing deficiency and toxicity symptoms in plants (Philipson, 1953). Important factors influencing the adsorption and removal of boron from the soil appear to be the pH of the system (Hingston, 1964;Mezuman and Keren, 1981;Sims and Bingham, 1967), the type of clay minerals (Hingston, 1964;Keren and Mezuman, 1981;Sims and Bingham, 1967), the type of exchangeable ions Parks and White, 1952), and wetting and drying cycles (Biggar and Fireman, 1960;. However, it is still not clear what specific role the clay minerals, the exchangeable cations, and the solution composition play in this process.…”
Section: Introductionmentioning
confidence: 99%
“…estimated a total boron adsorption capacity of 6.02/xmole/g for Na-montmorillonite. However, because Keren and Mezuman (1981) estimated different values for maximum boron adsorption for the Ca form of montmorillonite and illite (11.8 and 15.1/xmole/g, respectively), it is possible that additional factors influence boron adsorption. Pissarides et al (1968) showed that the exchangeable cations influenced the amount of phosphate that could be adsorbed on the edge sites of clay minerals.…”
Section: Introductionmentioning
confidence: 99%